Perkembangan Usahatani Pala Di Desa Wioi Kecamatan Ratahan Timur Kabupaten Minahasa Tenggara - Rako, Serin Deri; Tambas, Jane Sulinda; Pakasi, Caroline Betsy Diana (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to identify and describe the development of nutmeg farming in Wioi Village, East Ratahan District, Southeast Minahasa Regency. The data used in this study are primary data and secondary data. Primary data collection was obtained from field surveys and interviews with nutmeg farmers in Wioi Village. Field surveys using questionnaires, secondary data were obtained from government agencies, namely the Southeast Minahasa Agriculture Office, the Wioi Village office, the Ratahan Timur District Office, journals, theses and books. The results of this study indicate that the development of nutmeg farming in Wioi Village, Ratahan Timur District, Southeast Minahasa Regency has not yet developed, seen from several factors such as nutmeg cultivation, human resource (HR) factors, planning factors, farming results, processing factors, government assistance factors and development factors, namely factors of nutmeg farming opportunities, organizational factors and marketing and sales factors.